2020
DOI: 10.18632/aging.102845
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 gene rs10204525 and rs7421861 polymorphisms are associated with increased risk and clinical features of esophageal cancer in a Chinese Han population

Abstract: Programmed death-1 (PD-1) polymorphisms have been associated with esophageal cancer risk. Here, the aims of this case-control study were to explore whether three PD-1 polymorphisms (rs10204525, rs7421861, and rs36084323) were related with the risk and clinical features of esophageal cancer in Chinese Han subjects (n = 814 cases and 961 controls). We found that rs10204525 and rs7421861, but not rs36084323, conferred increased susceptibility to esophageal cancer. Subgroup analysis revealed that all three loci in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…However, two of them ( 163 , 174 ) showed a decreased risk for PD-1.6 G/G individuals (OR = 0.59 and OR = 0.68, respectively) (in the study by Qiu et al. ( 174 ) deviation from HWE was observed in controls), while Zang et al ( 175 ) reported the opposite effect—carriage of PD-1.6*G allele was associated with increased risk of esophageal cancer (OR = 1.26). Moreover, in this study individuals with PD-1.6 G/G genotype and carriers of PD-1.6*G allele had, respectively, higher TNM stage (OR = 1.81) and higher risk of distant metastasis (OR = 1.67) ( 175 ).…”
Section: Programmed Cell Death Proteinmentioning
confidence: 94%
See 4 more Smart Citations
“…However, two of them ( 163 , 174 ) showed a decreased risk for PD-1.6 G/G individuals (OR = 0.59 and OR = 0.68, respectively) (in the study by Qiu et al. ( 174 ) deviation from HWE was observed in controls), while Zang et al ( 175 ) reported the opposite effect—carriage of PD-1.6*G allele was associated with increased risk of esophageal cancer (OR = 1.26). Moreover, in this study individuals with PD-1.6 G/G genotype and carriers of PD-1.6*G allele had, respectively, higher TNM stage (OR = 1.81) and higher risk of distant metastasis (OR = 1.67) ( 175 ).…”
Section: Programmed Cell Death Proteinmentioning
confidence: 94%
“…( 174 ) deviation from HWE was observed in controls), while Zang et al ( 175 ) reported the opposite effect—carriage of PD-1.6*G allele was associated with increased risk of esophageal cancer (OR = 1.26). Moreover, in this study individuals with PD-1.6 G/G genotype and carriers of PD-1.6*G allele had, respectively, higher TNM stage (OR = 1.81) and higher risk of distant metastasis (OR = 1.67) ( 175 ). Taking into consideration the inconsistent results presented above as well as the fact that there was no evidence of association between this SNP and overall cancer risk—more research on this issue is needed.…”
Section: Programmed Cell Death Proteinmentioning
confidence: 99%
See 3 more Smart Citations